Pengembangan E-Modul dengan Pendekatan Saintifik mengunakan FlipHTML5 pada Pembelajaran Menulis Teks LHO berbasis Kearifan Lokal Banyuwangi untuk Kelas X SMK - Ghina Febyta Larasati; Arief Rijadi; Inno Cahyaning Tyas (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2025)
The limitation of learning materials that focus solely on structure and linguistic aspects demonstrates the need for the development of teaching materials that encourage students to think scientifically in a comprehensive manner, starting from observation to report writing. This study aims to assist students in understanding report text materials more effectively as well as to contribute to the preservation of local wisdom. The e-module on observation report texts based on local wisdom is in line with the objectives of the national curriculum, which emphasizes character development and cultural understanding. This research belongs to the category of Research and Development (R&D). The research design employed the 4-D Model (Four-D Models) by Thiagarajan, which consists of four stages: define, design, develop, and disseminate. The data in this study comprise verbal and numerical data. Verbal data were obtained through expert and practitioner validation in the form of feedback and suggestions, while numerical data were derived from assessments conducted by validators and student questionnaires. The results of the feasibility percentage calculation of the e-module based on expert and practitioner validation yielded an average of 87%. Meanwhile, the feasibility percentage based on students’ responses reached an average of 92%. These percentages demonstrate that the e-module of observation report texts based on the local wisdom of Banyuwangi for Grade X vocational high school students is highly feasible and can be implemented in the learning process.